Animal Behaviour [Working Title] 2019
DOI: 10.5772/intechopen.84872
|View full text |Cite
|
Sign up to set email alerts
|

The Disturbed Habitat and Its Effects on the Animal Population

Abstract: Changes in the "habitat" may interfere with the normal functioning of all biological systems. The existence of relationships between environmental changes and health in humans and animal species is well known and it has become generally accepted that poor health affects the animal's natural behaviors and animal welfare and, consequently, food safety and animal production quality. Microclimate alterations, husbandry-management conditions, quality of human-animal interactions, feeding systems, and rearing enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
(36 reference statements)
1
3
0
Order By: Relevance
“…Our study confirms this relation and further reveals that grassland specialists are the first to disappear from intensively grazed grasslands, since we found that the number of grassland specialists was lower in intensively grazed grasslands compared to those mown or abandoned. Our results also support the concern of many Romanian ecologists towards the increasing problem of overgrazing in the last decade (Roman et al, 2019). According to our findings, besides current management, land use history had a marked effect on the species composition and diversity of the studied grasslands.…”
Section: Discussionsupporting
confidence: 89%
“…Our study confirms this relation and further reveals that grassland specialists are the first to disappear from intensively grazed grasslands, since we found that the number of grassland specialists was lower in intensively grazed grasslands compared to those mown or abandoned. Our results also support the concern of many Romanian ecologists towards the increasing problem of overgrazing in the last decade (Roman et al, 2019). According to our findings, besides current management, land use history had a marked effect on the species composition and diversity of the studied grasslands.…”
Section: Discussionsupporting
confidence: 89%
“…The plumage conditions and body lesions confirmed that the more static genotypes (M and CY) also exhibited the lowest scores. Accordingly, it has been reported that these body lesions are associated with the contact of the body, mainly the plumage of the breast and the feet, with the humid and soiled bedding [24].…”
Section: Discussionmentioning
confidence: 99%
“…Although the hippocampus is a common brain area for the consolidation process of both types of memory, the functional network for each includes different adjacent areas whose process of both maturation and aging varies in a multifactorial manner and at different temporal levels (de Oliveira et al, 2011 ; Jacobs et al, 2015 ). From an evolutionary point of view, young and adult animals face ecological pressures with adaptive solutions that can be different but equally effective (Martins, 2011 ; Croft et al, 2015 ; Capucchio et al, 2019 ). With aging, ecological demands change, so do their adaptive strategies and the physiological and neural mechanisms that evolve to support them (Austad, 1997 ; Rovee-Collier and Cuevas, 2009 ; Martins, 2011 ).…”
Section: Discussionmentioning
confidence: 99%